Top Incomes : a Global Perspective. - Atkinson, A. B. (Anthony Barnes), 1944-2017 (OUP Oxford, 2010)
A rapidly growing area of economic research investigates the top of the income distribution using data from income tax records. This volume brings together studies of top incomes for twelve countries from around the world, including China, India, Japan, Argentina and Indonesia. Together with the first volume, published in 2007, the studies cover twenty two countries. They have a long time span, the earliest data relating to 1875 (for Norway), allowing recent developments to beplaced in historical perspective. The volume describes in detail the source data and the methods employed. It will be a.